2013
DOI: 10.1002/ggge.20290
|View full text |Cite
|
Sign up to set email alerts
|

Strong sediments at the deformation front, and weak sediments at the rear of the Nankai accretionary prism, revealed by triaxial deformation experiments

Abstract: [1] Nineteen whole-round core samples from the Nankai accretionary prism (IODP Expeditions 315, 316, and 333) from a depth range of 28-128 m below sea floor were experimentally deformed in a triaxial cell under consolidated and undrained conditions at confining pressures of 400-1000 kPa, room temperature, axial displacement rates of 0.01-9.0 mm/min, and up to axially compressive strains of 64%. Despite great similarities in composition and grain size distribution of the silty clay samples, two distinct ''rheol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 81 publications
1
25
1
Order By: Relevance
“…An intact sample of the siliceous mudstone from between the décollement and pelagic clay at Site C0019, which correlates with the diatomaceous claystone at Site 436, exhibited a cohesion value of 220 kPa . In comparison, measured cohesion of mudstones from Sites C0011 and C0012 along the Kumano transect at the Nankai Trough ranges from 13 to 160 kPa (Ikari et al, 2013a), consistent with calculated cohesion values of 35 and 41 kPa for two samples from these sites (Stipp et al, 2013). There is a large amount of amorphous silica in the Japan Trench mudstone unit, up to ~60% at both Sites C0019 and 436 (Kameda et al, 2015a), which might indicate advanced cementation.…”
Section: Diagenetic Effectssupporting
confidence: 74%
See 2 more Smart Citations
“…An intact sample of the siliceous mudstone from between the décollement and pelagic clay at Site C0019, which correlates with the diatomaceous claystone at Site 436, exhibited a cohesion value of 220 kPa . In comparison, measured cohesion of mudstones from Sites C0011 and C0012 along the Kumano transect at the Nankai Trough ranges from 13 to 160 kPa (Ikari et al, 2013a), consistent with calculated cohesion values of 35 and 41 kPa for two samples from these sites (Stipp et al, 2013). There is a large amount of amorphous silica in the Japan Trench mudstone unit, up to ~60% at both Sites C0019 and 436 (Kameda et al, 2015a), which might indicate advanced cementation.…”
Section: Diagenetic Effectssupporting
confidence: 74%
“…Intact samples preserve in situ effects such as fabric or cementation; however, for other boreholes in the Nankai Trough, some studies have found that these effects on friction are small (Ikari and Saffer, 2011;Saffer et al, 2012). The Nankai data set is supplemented by triaxial experiments on an intact sample of LSB mudstone from Site 1173(Bourlange et al, 2004 and intact samples from the ash-rich USB facies at Sites C0011 and C0012 (Stipp et al, 2013). We note that the values from Stipp et al (2013) are reported as a coefficient of internal friction.…”
Section: Friction Of Nankai Trough Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stipp et al, 2013) show variable sample compositions ( Table 2). The content of lithics is highly variable across the sample set and ranges between 1.8 and 46.8%.…”
Section: Sample Compositionsmentioning
confidence: 99%
“…Natural (experimentally undeformed) core samples as well as experimentally deformed samples were used for texture investigation in this study. Experimental samples were deformed under consolidated-undrained conditions in a triaxial apparatus (for further details on the experimental deformation see Stipp et al, 2013).…”
Section: Geological Setting and Sample Descriptionmentioning
confidence: 99%